THE EVOLVEMENT OF BRAND IDENTITY OF LANGKAWI ISLAND, MALAYSIA - Mohd Yusof, Mohd Fadil; Ismail, Hairul Nizam (PLANNING MALAYSIA, 2016)
The purpose of this paper is to investigate the brand identity development efforts of Langkawi Island as one of the most prominent and well-guarded tourism destinations in Malaysia. It will be viewed from the historical perspectives for the last 35 years since the 1980s until the present time as to how this involvement influences the formation of its brand identity and later, the existing destination image. Based on in-depth interviews with eleven different levels of managers of separate divisions for destination management organizations (DMOs) in Langkawi Island, Malaysia, theoretically, the findings provide an opportunity to expand the knowledge of destination brand identity development and the involvement of DMOs in influencing image making over time. Practically, the findings indicate three key important antecedents of brand identity development efforts related to: (1) the effects from multiple positioning themes and slogans, (2) the important of brand coordination, and (3) brand leadership issue. These empirical findings provide new insights into enhancing the theoretical aspect of managing a destination brand, including its close relationship with issues faced by destination marketing organizations in managing destination branding strategy. Thus, using the case study of Langkawi Island, the context of multiple identities or image fragmentation is important to be understood due to the different perceived ideas on how the image should be projected according to stakeholders and market segmentation.